2014
DOI: 10.1152/jn.00621.2013
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization patterns suggest different functional organization in parietal reach region and dorsal premotor cortex

Abstract: Chakrabarti S, Martinez-Vazquez P, Gail A. Synchronization patterns suggest different functional organization in parietal reach region and dorsal premotor cortex. J Neurophysiol 112: 3138-3153, 2014. First published September 17, 2014 doi:10.1152/jn.00621.2013.-The parietal reach region (PRR) and dorsal premotor cortex (PMd) form part of the fronto-parietal reach network. While neural selectivity profiles of single-cell activity in these areas can be remarkably similar, other data suggest that both areas serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 120 publications
(130 reference statements)
1
8
0
Order By: Relevance
“…Two spectral components dominated the LFP signals: the beta-band (13–28 Hz, LFP-beta) and frequencies lower than 10 Hz (LFP-LF). Consistent with our previous observations ( Chakrabarti et al 2014 ), LFP-beta was stronger in PRR than PMd, as obvious already from simultaneously recorded raw data (Fig. 2 A ; see Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Two spectral components dominated the LFP signals: the beta-band (13–28 Hz, LFP-beta) and frequencies lower than 10 Hz (LFP-LF). Consistent with our previous observations ( Chakrabarti et al 2014 ), LFP-beta was stronger in PRR than PMd, as obvious already from simultaneously recorded raw data (Fig. 2 A ; see Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
“…LFP-beta in PMd, instead, while known to be spatially selective during evoked potentials ( Mehring et al 2003 ; O’Leary and Hatsopoulos 2006 ), was strongly attenuated in power during sustained memory phases, especially compared with PRR (Fig. 2 and ( Chakrabarti et al 2014 )). Correspondingly, Salazar and colleagues showed that beta-range interaction was dominated by parietal-to-frontal influences (parietal senders, frontal receivers), and that frontoparietal beta-frequency coherence was content-specific ( Salazar et al 2012 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Combination of spiking activity and LFP is often used to study rhythmic neuronal synchronization since spike-LFP measures are more sensitive than spike-spike synchronization measures (Vinck et al, 2012; Chakrabarti et al, 2014). To this end Brainstorm, Chronux, FieldTrip and Elephant implement a spike-field coherence (SFC), a frequency-domain pairwise non-directional measure.…”
Section: Toolboxes With Synchronization and Connectivity Analysis Toolsmentioning
confidence: 99%